Prepositional phrases analysis Found in bbc news based on Systemic functional linguistics perspective - Astiari, Komang (International Journal of Linguistics and Discourse Analytics, 2025)
This study analyzed the prepositional phrases appearing in bbc.com/news from the systemic functional linguistics perspective. The method applied was library research using observation and note-taking technique. Prepositional phrase is a phrase which is started with a preposition followed by noun or pronoun. Additionally, in language metafunction, prepositional phrases have three different functions namely ideational, interpersonal, and textual metafunction. The outcome gained from this research was that the prepositional phrases appear in BBC News have different purposes based on three metafunctions. Firstly, in ideational metafunction, prepositional phrases were realized by circumstance of location, time, duration, manner, purpose, and point of view. Then, in interpersonal metafunction, prepositional phrases aim at creating clarity, indicating relationship between people, expressing feeling and intention effectively. Lastly, in textual metafunction, prepositional phrases help to give cohesion and coherence into the text.